Design Of Web Based LMS (Learning Management System) in SMAN 1 Kampar Kiri Hilir - Muhardi Muhardi; Sakroni Indra Gunawan; Yuda Irawan; Yesica Devis (Journal of Applied Engineering and Technological Science (JAETS), 2020)
Learning Management System appears as a solution to the many problems that arise due to limited time, place and the number of meetings between teacher and student. Learning Management System as a tool in the learning process offers several advantages so that it can solve problems that often arise in the learning process. Based on the limited number and time of meetings, a web-based Learning Management System was built by using the PHP programming language and MySQL Using the Waterfall Model Method. The result has been developed a Learning Management System for SMA NEGERI 1 KAMPAR KIRI HILIR with facilities as a medium for the dissemination of subject matter, media for the distribution of assignments, and as a media for student discussion forums. In this Learning Management System application has 3 admin actors, teachers, students. The admin has the duty as an elearning application manager to manage the application so that it can run well. The admin manages curriculum data, semester years, teachers, students, subjects. The teacher gives the material and assignments done by students, while students will work on assignments uploaded by the teacher and download the material that has been uploaded by the teacher. Learning Management System application as a support for learning activities, because schools are able to carry out learning activities not only teaching in the classroom. By creating learning media through the Learning Management System website in SMA NEGERI 1 KAMPAR KIRI HILIR, teacher and student interaction is increasing.